2021
DOI: 10.21608/ejnf.2021.170317
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Citric, Acetic Acids or Their Mixture on Broiler Chicks Performance, Carcass Characteristics and Some Intestinal Histomorphological Parameters

Abstract: total number of 120, 1d old unsexed chicks were randomly distributed and divided equally into 4 dietary treatment groups with 3 replicates each. All broiler chickens were kept under similar managerial conditions. Basal starter and finisher diets were supplemented with two types of organic acids as follows: T1: basal diet (control, without supplementation), T2: basal diet + 2% citric acid (CA), T3: basal diet + 1% acetic acid (AC) and T4: basal diet + 1% citric acid + 0.5% acetic acid. Two cornsoybean based bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…The latest authors revealed that layer-fed diets containing 500 and 3000 ppb nanometric chromium picolinate produced eggs with low yolk weight percentage. Laying hens fed on diets supplemented with zinc oxide nanoparticles achieved the highest significant improvement in egg shell quality, egg index, yolk and white quality, and HU compared to the control group [4]. The enhancement observed can potentially be attributed to the exceptional characteristics of nano-minerals, e.g., their remarkable biological availability, higher surface activity, improved mobility, increased solubility, and enhanced cellular uptake [63,115].…”
Section: Effect Of Nano-minerals On Egg Qualitymentioning
confidence: 99%
“…The latest authors revealed that layer-fed diets containing 500 and 3000 ppb nanometric chromium picolinate produced eggs with low yolk weight percentage. Laying hens fed on diets supplemented with zinc oxide nanoparticles achieved the highest significant improvement in egg shell quality, egg index, yolk and white quality, and HU compared to the control group [4]. The enhancement observed can potentially be attributed to the exceptional characteristics of nano-minerals, e.g., their remarkable biological availability, higher surface activity, improved mobility, increased solubility, and enhanced cellular uptake [63,115].…”
Section: Effect Of Nano-minerals On Egg Qualitymentioning
confidence: 99%